2017
DOI: 10.19030/ajee.v7i2.9895
|View full text |Cite
|
Sign up to set email alerts
|

Pierre Van Cortlandt Middle School Promotes Student STEM Interest

Abstract: The principal purpose of this investigation is to study the effect of robotic cooperative learning methodologies on middle school students’ critical thinking, and STEM interest. The semi-experimental inquiry consisted of ninety four six-grade students (forty nine students in the experimental group, forty five students in the control group), chosen by their principals. A critical thinking test was administered to evaluate the cognitive skills and STEM interest of the students. Instruction was implemented in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Events such as robot battles, maze-solving challenges, and collaborative projects enhance technical proficiency and instill a sense of achievement and resilience in participants. Beyond competitions, robotics clubs often extend their reach into community outreach programs, where students apply their knowledge to address real-world problems, fostering a sense of social responsibility (Mosley, Ardito, & Scollins, 2016). In conclusion, robotics clubs in K-12 education serve as catalysts for cultivating STEM enthusiasm among students.…”
Section: Robotics Clubs In K-12 Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Events such as robot battles, maze-solving challenges, and collaborative projects enhance technical proficiency and instill a sense of achievement and resilience in participants. Beyond competitions, robotics clubs often extend their reach into community outreach programs, where students apply their knowledge to address real-world problems, fostering a sense of social responsibility (Mosley, Ardito, & Scollins, 2016). In conclusion, robotics clubs in K-12 education serve as catalysts for cultivating STEM enthusiasm among students.…”
Section: Robotics Clubs In K-12 Educationmentioning
confidence: 99%
“…Not all students thrive in the same learning environment. While robotics clubs emphasize hands-on, experiential learning, some students may prefer alternative approaches (Eguchi, 2016;Mosley et al, 2016). Ensuring inclusivity for diverse learning styles is a challenge as educators strive to create an environment that caters to the diverse student body's varied needs and preferences.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…1 The method of teaching learning process [3] The other method show that critical thinking method in robot education in better than problem based learning. It can enhance student by cooperative learning [5]. Further, the effective method in study robotic is taken place in classroom, where they can build their own concepts and themes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increase in the use of robots in STEM education. The results of the research on robotics in STEM education also show that such practices improve learners' creative thinking and problem-solving skills, make learning fun, promote positive attitudes, and increase motivation toward education (Karim, Lemaignan, & Mondada, 2015;Mosley, Ardito, & Scollins, 2016;Özdemir, Çelik, & Öz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the literature is concerned, the popularity of robotics and programming are increasing in educational environments (Alimisis, 2013;Xia & Zhong, 2018;Ucgul & Cagiltay, 2014;Hubwieser et al, 2015;Karim, Lemaignan, & Mondada, 2015;Mosley, Ardito, & Scollins, 2016;Özdemir, Çelik, & Öz, 2009). The literature review suggested that improving learning for ICT teachers enrolled in the "Embedded Systems and Robotic Applications" course at the graduate level was important.…”
Section: Introductionmentioning
confidence: 99%